Assessing Wall Tie Deterioration in Masonry Veneer Wall Through Vibration-Based Damage Identification Methods - Chee Yin Lam; Mark Masia; Igor Chaves; Md Akhtar Hossain; John Vazey (Buildings)
Experimental modal analysis has proven effective in damage identification of civil structures but has not been extensively applied to multi-leaf masonry structures, particularly in the context of wall tie inspection. This paper investigates the applicability of non-destructive, vibration-based damage identification methods to a one-storey masonry veneer wall to detect wall tie deterioration based on changes in modal parameters. An impact hammer was used to collect vibration data from eight different wall tie deterioration test cases by disconnecting the wall ties at various locations. The downshift of natural frequencies was recorded for all deterioration test cases, and a reduction of up to 38% was observed when the top row of wall ties was disconnected, highlighting the importance of wall ties to the overall stiffness of the masonry veneer wall system. In terms of damage localisation accuracy, the parameter-based method performed the best by successfully identifying seven out of eight damaged scenarios without additional noise. The findings show that the detection of wall tie deterioration using non-destructive, vibration-based damage identification methods is viable, providing an alternative wall tie inspection method with significant benefits to infrastructure management, thereby enhancing safety, efficiency, and sustainability in maintaining and preserving masonry veneer walls.